Nutritional transition period in early larvae Clarias gariepinus - Hou Chew, Ha; Siew Ing, Nguang (Malaysian Society of Analytical Sciences, 2015)
The nutritional transition period of Clarias gariepinus were described based on the early development from hatching to 120 hours after hatching (hAH) reared at 27.5-28.6oC. Newly hatched larvae had a large greenish yolk sac volume (0.99+0.31 mm3) located below a straight undeveloped digestive tract, mouth not opened, eyes unpigmented and the larvae lie on the bottom of rearing tank. During endogenous feeding period, the larval feeding system has developed rapidly with development oesophagus. Yolk sac were not completely depleted at the onset of exogenous feeding (36 hAH, 0.19±0.11 mm3), and a period of mixed nutrition was observed up to 68 hAH when yolk was completely exhausted. Yolk sac volume was significantly different by time at hatching, 6, 12 and 18 to 36 hAH (ANOVA, P<0.05). At 36 hAH, the larvae commenced feeding once morphologically developed with opened anus, functional jaw and intestine, and demonstrated horizontally swimming. The rudimentary chemoreceptors like olfactory organs and taste buds that were found on the barbels and oral cavity assisted in food detection and commenced feeding without vision. Due to the cannibalistic behaviour at early stage, feed are suggested to be provided during 36 hAH and avoided delay feeding in the larval rearing.